Empowerment of Coastal Communities in Cultural and Environmental Preservation (Karolahan Traditional Village, West Tianyar, Karangasem) - I Wayan Rideng; I Made Minggu Widyantara; Desak Gede Dwi Arini (Law Doctoral Community Service Journal, 2022)
Indonesia is a maritime country, this is shown through its territory consisting of islands with very long coastal boundaries. Coastal and coastal areas are very rich in marine life and others. Aside from being a place of livelihood for fishermen, it is also a place for traditional salt farmers whose production has a specificity. Beaches in Bali not only have economic and social functions, but also have cultural aspects or religious functions. For this reason, the existence of beaches and their coasts is very important and strategic, it is necessary for people who live on the coast to be empowered in order to preserve culture and the environment. Because every traditional village in Bali there is a ceremony process in the coastal area, including the Karolahan Traditional village, Tianyar village. With these conditions, there needs to be an understanding and knowledge of the existing community empowerment efforts on the coast, as well as playing a role in environmental conservation efforts. Activities that need to be carried out through legal counseling to Krama Desa Adat, considering that fishermen and traditional salt farmers are part of Krama Desa Adat.